Ethiopia: spectacular response of indigenous clovers to phosphates - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Two researchers from the International Breeding Centre in Africa (CIPEA) presented evidence of the extraordinary response of indigenous African clovers to small to moderate applications of phosphorus. The clovers with the most potential came from...